Artificial intelligence integration in Bangladeshi university EFL classrooms: Perceptions, practices, and challenges - Md. Tareq Jamil; Md Nazmul Haque; Md. Maidul Islam (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2026)
Although the use of artificial intelligence (AI) in education is increasing worldwide, there is a lack of studies examining the integration of AI into Bangladeshi University EFL classrooms from both students’ and instructors’ perspectives. Grounded in the Technology Acceptance Model (TAM; Davis, 1989), this convergent mixed-methods study investigates perceptions, patterns of use, and perceived challenges related to AI tools in university-level EFL classrooms in Bangladesh. 41 participants, consisting of 30 students and 11 instructors from public and private universities, participated in this study. Data were collected through an online questionnaire and analyzed using descriptive statistics and thematic analysis. The findings suggest that AI tools, particularly ChatGPT and Gemini, are commonly used by participants to support language learning and teaching activities. Both university students and instructors generally perceive AI as helpful for improving learning efficiency and supporting the development of language skills. However, participants also expressed concerns about limited training, potential inaccuracies in AI-generated content, ethical considerations, and the risk of over-reliance on this tool. Thematic analysis further highlights several conditions that may support more effective AI integration in EFL contexts, including the need for training opportunities, improved technological infrastructure, clearer institutional policies, alignment with curriculum goals, and supportive attitudes among instructors.